2010
DOI: 10.1016/j.brainres.2009.09.036
|View full text |Cite
|
Sign up to set email alerts
|

The locus coeruleus: A key nucleus where stress and opioids intersect to mediate vulnerability to opiate abuse

Abstract: The interaction between the stress axis and endogenous opioid systems has gained substantial clinical attention as it is increasingly recognized that stress predisposes to opiate abuse. For example, stress has been implicated as a risk factor in vulnerability to the initiation and maintenance of opiate abuse and is thought to play an important role in relapse in subjects with a history of abuse. Numerous reports indicating that stress alters individual sensitivity to opiates suggest that prior stress can influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 154 publications
(217 reference statements)
2
99
0
Order By: Relevance
“…As reviewed previously (Aston-Jones and Bloom 1981a; Aston-Jones et al 1991b;Berridge and Waterhouse 2003;Van Bockstaele et al 2010), LC is a discrete, compact, homogeneous nucleus, consisting of almost exclusively NE neurons. The major inputs to LC are from the medullary nucleus paragigantocellularis (PGi) and nucleus prepositus hypoglossus, and LC outputs are widespread including forebrain, cerebellum, brainstem, and spinal cord ( Fig.…”
Section: Locus Coeruleus Backgroundmentioning
confidence: 84%
“…As reviewed previously (Aston-Jones and Bloom 1981a; Aston-Jones et al 1991b;Berridge and Waterhouse 2003;Van Bockstaele et al 2010), LC is a discrete, compact, homogeneous nucleus, consisting of almost exclusively NE neurons. The major inputs to LC are from the medullary nucleus paragigantocellularis (PGi) and nucleus prepositus hypoglossus, and LC outputs are widespread including forebrain, cerebellum, brainstem, and spinal cord ( Fig.…”
Section: Locus Coeruleus Backgroundmentioning
confidence: 84%
“…In addition to mediating the dysphoric responses of stress, p38 MAPK activation within the DRN has also been found to contribute to depressive-like and drug-seeking behaviors [80] . The locus coeruleus (LC) is one of the primary sources of norepinephrine (NE) in the forebrain [81] . Dynorphin and κ opioid receptors are coexpressed within the LC on noradrenergic (NA) neurons [67,[82][83][84][85] .…”
Section: Brain Regions Involved In κ Opioid Receptor-mediated Anxietymentioning
confidence: 99%
“…Ai-Hasani et al (2013) first reported that κ opioid receptors within the LC NA nuclei modulate the reinstatement of cocaine place preference through a noradrenergic mechanism [88] . Because the LC-NE system is a critical stress response system [81] , κ opioid receptor pathway interactions with the NA system may influence κ opioid receptor-mediated aversion and anxiety-like behaviors. Evidence supports a model in which the dynorphin/κ opioid receptor system and CRF coordinate in stressinduced anxiety behaviors.…”
Section: Brain Regions Involved In κ Opioid Receptor-mediated Anxietymentioning
confidence: 99%
“…KORs are known to be expressed in the LC and are highly implicated in stress and KOR-induced reinstatement of nicotine, alcohol, and cocaine preference and self-administration ( Van Bockstaele et al, 2010;Bruchas et al, 2010). In this experiment, we isolated the effects of KOR activation on reinstatement by determining the necessity of KOR expression within the LC for U50-induced reinstatement to cocaine preference.…”
Section: Kor Antagonism In the Lc Reduces The Magnitude Of Kor-inducementioning
confidence: 99%
“…Furthermore, KOR agonist injection into the LC attenuates phasic LC discharge events evoked by stimuli that engage LC afferents, suggesting that KORs presynaptically inhibit afferent inputs into the LC system. KOR is also thought to be expressed directly on NA neurons to inhibit NE release, as evidenced by anatomical and physiological studies ( Van Bockstaele et al, 2010;Limberger et al, 1986). However, it is important to note that few, if any, studies have examined the cell type and function of KOR signaling within the LC, and future studies in vitro and in vivo with cell type conditional KOR KO (Tejeda et al, 2013;Van't Veer et al, 2013), cell type-selective restoration, and local circuit identification will be needed to advance our understanding of dynorphin/KOR's role within cell types in the LC.…”
Section: Na -Kor Interactions In Kappa Opioid-mediated Cocaine Reinstmentioning
confidence: 99%